Research on Aesthetic Education Practice in Higher Education - Wang, Jianqing (Journal of Research in Vocational Education, 2025)
One of the goals of higher education in China is to cultivate college students with comprehensive development in morality, intelligence, physical fitness, aesthetics, and labor skills. Among them, cultivating college students with aesthetic ability and noble aesthetic sentiment is an important part of this goal. Based on the experience of a college student worker for many years, this paper discusses the situation of aesthetic education practice in higher education from three aspects: the analysis of the situation of aesthetic education practice in higher education, the discussion of the causes of aesthetic education practice problems in higher education, and the solutions to the problems in aesthetic education practice in higher education.